The Association of Homocysteine with Placenta-Mediated Pregnancy Complications - Chaudhry, Shazia Hira (Université d'Ottawa / University of Ottawa, 2019)
Background: Preeclampsia, small for gestational age (SGA), placental abruption, and fetal death are pregnancy complications linked to the utero-placental vasculature with serious consequences for maternal and infant well-being. Elevated homocysteine, a marker of cardiovascular disease risk, is postulated to play a role in placenta-mediated complications, but epidemiologic studies have reported inconsistent findings. The two primary objectives of this thesis were to 1: comprehensively investigate the association of homocysteine with placenta-mediated complications and examine modifying effects of pre-specified factors on this association, and 2: comprehensively investigate determinants of maternal homocysteine during pregnancy. Methods: A systematic review and meta-analysis of prospective studies was conducted to address thesis objective 1. The Ottawa and Kingston (OaK) Birth Cohort, a prospective cohort study that recruited pregnant women between 2002 and 2009, was used to address thesis objectives 1 and 2. Homocysteine concentration was measured between 12 and 20 weeks gestation. Analyses based on the OaK Birth Cohort consisted of multivariable regressions using restricted cubic splines to model associations with continuously distributed variables. Results: Objective 1: In an analysis of 7587 participants, a significant association between homocysteine concentration and a composite outcome of any placenta-mediated complication was observed (odds ratio (OR) for a 5 µmol/L increase: 1.63, 95% Confidence Interval (CI) 1.23-2.16) and SGA (OR 1.76, 95% CI 1.25-2.46), with potential modifying effects of the methylene tetrahydrofolate reductase (MTHFR) 677C>T variant (SGA) and high-risk pregnancy (preeclampsia). In the systematic review identifying 30 prospective cohort or nested case-control studies, a random effects meta-analysis of pooled mean differences in homocysteine between cases and controls in 28 studies revealed significantly higher means for SGA: 0.35 µmol/L (95% CI 0.19 to 0.51, I2=33%); and preeclampsia: 0.87 µmol/L (95% CI 0.52 to 1.21, I2=92%). Significant sources of heterogeneity were study region (SGA and preeclampsia), adjusting for covariates (preeclampsia), folate status (preeclampsia), and severity (preeclampsia). Objective 2: In 7587 OaK participants, factors related to favourable health status were associated with lower maternal homocysteine concentrations. Folic acid supplementation during pregnancy of >1 mg/day did not substantially increase serum folate concentration. Conclusion: This thesis suggests an independent effect of slightly higher homocysteine concentration in the early to mid-second trimester on the risk of any placenta-mediated complication, SGA, and preeclampsia. Modifying effects explain some of the variability in previous studies. Favourable preconception health status was associated with lower maternal homocysteine.
Keywords: homocysteine; placenta; hyperhomocysteinemia; birth cohort; pregnancy complication; MTHFR; folic acid; folate; small for gestational age (SGA); preeclampsia; placental abruption; pregnancy loss